Public education expenditure, institution development, and regional innovations: An empirical evidence from China - Chenhui Li; Xubei Lian; Zhi Zhang (Kiel Institute for the World Economy (IfW), 2018)
This paper investigates the relationship between government education expenditure and regional innovation, a key engine of China's long-term economic growth as the nation undergoes massive economic restructuring and deep transformations. In an attempt to inform a whole-of-government approach in promoting indigenous knowledge generation, the authors examined the effect of two additional institutional factors, financial market development and Intellectual Property protection, as well as their interaction with education expenditure on regional innovation levels. By employing a sample of provincial panel data from 1998 to 2014, the authors find a significant positive correlation between education expenditure and regional innovation levels, an effect most pronounced in the Western provinces of China. Their analysis also revealed that financial market development augments the pro-innovation effect of education spending whereas a stronger IP protection regime could potentially mitigate such effect. The findings indicate that government investments in education as well as the creation of a more developed financial landscape will be effective ways to enhance regional innovation levels. However, attention should be paid to the nuances of the current IP protection system as well as the conduct of market players to pre-empt exploitations and enable greater incentives for sustained innovations.
Keywords: I21; I28; O35; 330; education expenditure; innovation; financial market development; intellectual property protection